The Pengaruh Digital Learning Capability dan Professional Development Support terhadap Kinerja Talenta Dosen dengan Self-Efficacy sebagai Mediasi: The Influence of Digital Learning Capability and Professional Development Support on Lecturer Talent Performance with Self-Efficacy as a Mediator - Budiarti, Sari (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2025)
Changes in work patterns and the growing demands for digital competencies require organizations to enhance the quality of human resources, particularly in the context of talent development. This study is motivated by the importance of understanding the role of Digital Learning Capability and Professional Development Support in influencing Talent Performance, with Self-Efficacy acting as a mediating variable. The objective of this research is to analyze both the direct and indirect effects among these variables within the framework of digital and psychological-based talent performance development. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The sample consists of university lecturers, with a total of 150 respondents selected through purposive sampling. Data were collected using a structured questionnaire based on a Likert scale, and analyzed using the SmartPLS 4.0 software. The results indicate that Professional Development Support has a significant influence on both Self-Efficacy and Talent Performance, whereas Digital Learning Capability does not have a significant direct effect on either variable. Moreover, Self-Efficacy demonstrates a very strong influence on Talent Performance and serves as a key mediating variable between professional development support and talent performance. These findings reinforce the critical role of professional development as a primary strategy for building individual confidence, which positively impacts performance. The novelty of this study lies in its integration of digital learning capabilities with psychological constructs and performance within a single structural model that addresses the challenges of modern work transformation.